Alaskan Heteroptera (Hemiptera): new records, associated data, and deletions - Scudder, G. G.e.; Sikes, D. S. (Zootaxa, 2014)
Twenty-seven species of Heteroptera are recorded new to Alaska. Specimen data for ten additional species reported from Alaska without previously published data are also provided. Additionally, four species previously reported from the state are removed from the Alaska list of Heteroptera.